Debating Sharia : Islam, gender politics, and family law arbitration - Korteweg, Anna; Selby, Jennifer A. (University of Toronto Press, 2012)
"When the Islamic Institute of Civil Justice announced it would begin offering Sharia-based services in Ontario, a subsequent provincial government review gave qualified support for religious arbitration. However, the ensuing debate inflamed the passions of a wide range of Muslim and non-Muslim groups, garnered worldwide attention, and led to a ban on religiously based family law arbitration in the province. Debating Sharia sheds light on how Ontario's Sharia debate of 2003-2006 exemplified contemporary concerns regarding religiosity in the public sphere and the place of Islam in Western nation states